Knowledge of hearing screening among health workers at the health clinics in Kota Bharu district, Kelantan - Yusof, Aqma Nadira Mohd (Universiti Sains Malaysia, 2012)
Hearing screening is very important to be done. It is done to detect among apparently healthy person, those individuals who demonstrate a probability for having a disease or condition, so they may be referred for further evaluation (ASHA, 1997). This survey is aimed to determine the overall view about health workers (medical officers, medical assistants and nurses) knowledge regarding hearing screening at the health clinics in Kota Bharu, Kelantan District. Questionnaires were distributed to the 180 health workers by hand. They were asked to fill in the questionnaires and the researcher collects it after one week. Only 145 of them (80.2%) responded and this was considered sufficient. From the study, it showed that there is no significant difference in knowledge of hearing screening across categories of occupation (p= 0.135). Results also showed that there is significant correlation between duration of work experience and knowledge of hearing screening (p= 0.006) but the correlation is weak (r= 0.228). There is significant correlation between age and knowledge of hearing screening (p= 0.04) but the correlation is also weak (r= 0.167). In general, the knowledge of hearing screening among health workers is seem to be adequate, at least in this study. Respondents claimed that not enough equipment (66.2%), noisy environment (53.1%), not enough staff (35.2%), not enough time (19.3%) and other reasons (11.7%) like hearing screening is not their scope of practice and they did not learn about hearing test are the problems faced by health workers to perform hearing screening at their clinic. Most of the respondents (85%) showed their interest to perform the hearing test at their clinic if there are chances to do it.